User Orientation as an Organizational Principle: the Warsaw Experience - Stepniak, Jolanta (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2002)
Warsaw University Library (WUL) was already more than 180 years old, with a traditional and stable organization, when it made its first attempts to bring modern library concepts to a newly-constructed building in December 1999. It was high time for a change. Nineteenth-century, monumental construction could no longer keep pace with those goals established for the university community. Overloaded stacks were partly inaccessible; an underdeveloped local network was permanently overworked; and small reading rooms were inadequate for our growing number of students. Even great commitment by library staff was insufficient to users’ requirements and newly-created tasks.